2013
DOI: 10.1557/jmr.2013.283
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation damage of single crystal, coarse-grained, and nanograined copper under helium bombardment at 450 °C

Abstract: The irradiation damage behaviors of single crystal (SC), coarse-grained (CG), and nanograined (NG) copper (Cu) films were investigated under Helium (He) ion implantation at 450°C with different ion fluences. In irradiated SC films, plenty of cavities are nucleated, and some of them preferentially formed on growth defects or dislocation lines. In the irradiated CG Cu, cavities formed both in grain interior and along grain boundaries; obvious void-denuded zones can be identified near grain boundaries. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 49 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Yu et al [4] have observed that reducing grain size lowers the density of He bubbles in Fe irradiated with He ions. Likewise, Han et al [5] observed that the density and size of cavities were reduced in nanograined Cu as compared to coarse-grained Cu when subjected to He irradiation. Similarly, Alsabbagh et al [6] observed a reduction in radiation-induced hardening and embrittlement in ultra-fine-grained steel as compared to coarse-grained steel, while Sun et al [7] quantified the reduction in swelling and swelling rate in 304 L stainless steel when using an ultra-fine-grained structure.…”
Section: Introductionmentioning
confidence: 93%
“…Yu et al [4] have observed that reducing grain size lowers the density of He bubbles in Fe irradiated with He ions. Likewise, Han et al [5] observed that the density and size of cavities were reduced in nanograined Cu as compared to coarse-grained Cu when subjected to He irradiation. Similarly, Alsabbagh et al [6] observed a reduction in radiation-induced hardening and embrittlement in ultra-fine-grained steel as compared to coarse-grained steel, while Sun et al [7] quantified the reduction in swelling and swelling rate in 304 L stainless steel when using an ultra-fine-grained structure.…”
Section: Introductionmentioning
confidence: 93%
“…Due to the high density of grain boundaries and interfaces, a number of nanostructured materials have displayed a higher tolerance to radiation damage compared to their coarse-grained counterparts. For example, reduced defect density and increased radiation tolerance in nanocrystalline metals has been reported for ion irradiated Fe [3,9], Pd [10], Cu [11], W [12], and Ni [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafine-grained single phase materials have been shown to trap helium at grain boundaries, but they are not particularly efficient and can coarsen at high temperatures or during irradiation [10][11][12][13]. Interphase boundaries in oxide dispersion strengthened (ODS) steels have also been shown to be good defect sinks, and they are stable in the extreme environment of a nuclear reactor [14][15][16].…”
Section: Introductionmentioning
confidence: 99%